The fresh energy cookbook : detox recipes to supercharge your life - Rose, Natalia. frey50; Choi, Doris (Guilford, Conn. : Lyons Press, 2013)
"A leading light in the alternative health community, Natalia Rose is widely recognized for her "detox diet" program. Her popular book, The Raw Food Detox Diet, is by now considered a classic of its genre. The Fresh Energy Cookbook is the essential companion guide for anyone who wants to bring those dietary principles to life in the comfort of their own kitchen. The emphasis is on living foods in digestible combinations, ideal for optimal cellular health, nutrition, energy, weight loss, and satisfaction"--
Foreword / Matthew Kenney -- The principles. The fundamentals ; Food combining ; How to use this book ; Creating your personalized meal plan -- Your kitchen. Tools and equipment ; Kitchen skills ; In Doris's pantry ; The market ; The visual palette: what color is your food? -- The recipes. Lemonades & herb waters ; Life force energy juices ; Smoothies ; Seed & nut milks ; Fruits ; Basic recipes ; Dressings, dips, sauces & spreads ; Raw wraps & rolls ; All salads considered ; Sandwiches ; Raw soups ; Cooked soups ; Raw main dishes ; Cooked main dishes ; Seafood ; Side dishes ; Snacks ; Desserts ; Your detox future.
Includes index.
Keywords: Detoxification (Health); Nutrition; COOKING / Health & Healing / Weight Control; COOKING / Courses & Dishes / General; Detoxification (Health); Nutrition; Cookbooks